2008
DOI: 10.1111/j.1365-2214.2008.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical fitness and motor competence in children

Abstract: These results are relevant to the work of maintaining and developing both sufficient physical fitness and motor competence in children as these factors are important contributors to their health and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
113
0
23

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 33 publications
(83 reference statements)
11
113
0
23
Order By: Relevance
“…Até, aproximadamente, os 10-11 anos de idade, não existem diferenças importantes na composição corporal que justifiquem a superioridade do sexo masculino em medidas de aptidão física 14,15 . Desse modo, as diferenças encontradas nessa faixa etária podem indicar um menor envolvimento com a prática regular de atividades físicas no sexo feminino, uma vez que existe uma forte relação entre o nível de aptidão física e a prática de atividades físicas de crianças e adolescentes [16][17][18][19] . A estabilização de desempenho no sexo feminino após os 11 anos foi verificada em outros estudos brasileiros 5,[20][21][22][23][24] .…”
Section: Discussionunclassified
“…Até, aproximadamente, os 10-11 anos de idade, não existem diferenças importantes na composição corporal que justifiquem a superioridade do sexo masculino em medidas de aptidão física 14,15 . Desse modo, as diferenças encontradas nessa faixa etária podem indicar um menor envolvimento com a prática regular de atividades físicas no sexo feminino, uma vez que existe uma forte relação entre o nível de aptidão física e a prática de atividades físicas de crianças e adolescentes [16][17][18][19] . A estabilização de desempenho no sexo feminino após os 11 anos foi verificada em outros estudos brasileiros 5,[20][21][22][23][24] .…”
Section: Discussionunclassified
“…One of these is motor competence (Clark & Metcalfe, 2002;Gallahue, Ozmun, and Goodway, 2012). Motor competence refers to the ability to execute diverse motor tasks in a skilful manner, which includes the coordination of both gross and fine motor skills (Gallahue, Ozmun, & Goodway, 2012;Haga, 2008). The role of motor competence in children's physical activity levels has been conceptualized in a theoretical model by Stodden et al (2008; recently revised by Robinson et al in 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The suggested four factors could be viewed as broader aspects of movement skills in the growth and refinement phase (Gabbard, 2004) and specialized movement phase (Gallahue & Ozmun, 1998) in relation to the already established basic movement categories of locomotor, object control, and stability skills in the fundamental movement skills (FMS) phase. The component of strength in Factor 1, here labeled strength and coordination skills , have in previous research shown to be related to good results in movement skill testing (e.g., Haga, 2008;Hands et al, 2009;Stodden et al, 2009;Thomas & French, 1985). A component of strength can be understood as an important part in movement skill development.…”
Section: Discussionmentioning
confidence: 99%
“…Movement competency has also proved to be important in terms of the physical fitness of children (Haga, 2008), adolescents (Hands, Larkin, Parker, Straker, & Perry, 2009) and young adults (Stodden, Langendorfer, & Roberton, 2009). Movement competence can generally be described as the ability to use voluntary movements in order to achieve a specific purpose or goal (Magill, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation